Secretory oviducts contribute to the high egg-laying rate of physogastric termite queens (Isoptera: Termitidae) - Costa-Leonardo, Ana Maria [UNESP]; Janei, Vanelize [UNESP]; da Silva, Iago Bueno [UNESP] (Elsevier, 2023)
Physogastric termite queens are characterized by a notorious enlargement of the abdomen triggered by an equal development of the ovaries. Other physogastry-related modifications have been reported on the fat body, cuticle, midgut, tracheal system, and hemolymph. Surprisingly, modifications on the lateral oviducts of these females, important sites for ovulation and egg transport, have received little attention. Here we took advantage of the high fecundity of physogastric queens in three termitid species to evaluate ovary development and also to compare the morphophysiological features of the lateral oviducts between early-mated and physogastric queens of Cornitermes cumulans. Older queens show well-developed ovaries, with numerous ovarioles connected to the lateral oviducts through pedicels. At these sites, several corpora lutea were observed, residual follicle cells from previous ovulation events. Such features were absent among early-mated queens and reflect then the maturity and ageing of the queens. Histological and histochemical analyses indicated that secretory activity of the lateral oviducts was also restricted to physogastric queens, in which proteins, but not polysaccharides, are secreted into the oviduct lumen. The likely function of these proteins, based on previous studies, is to lubricate the lateral oviducts and stimulate muscular contractions to the egg transport. The physogastry of termite queens is a notorious feature, characterized by several body modifications, especially concerning the ovaries. Our results shed light on the physogastry-related changes in the lateral oviducts of termite queens, as their increasing secretory activity is in agreement with the high number of eggs produced and transporting through these structures. Thus, such changes correspond to an important step allowing the high egg-laying rate shown by physogastric termite queens.
Keywords: Fecundity; Histochemistry; Ovarian development; Oviposition; Physogastry; Reproduction